SOCIAL ASPECTS OF EDUCATION IN EDUCATIONAL INSTITUTIONS - Rakhmatov Nuriddin Negkadamovich (Modern American Journals, 2025)
The article examines the system of continuous education, the main principles of state policy at all its stages. It recognizes the talents and abilities of our youth in the new Uzbekistan, the opportunities for their full realization, draws attention to the issues of studying and scientifically analyzing the spiritual heritage, reflecting and integrating it in the educational process of our youth, and gives its practical recommendations for the educational work of students of higher educational institutions.
Keywords: Economic, social, political reforms, man, labor, relations, socio-economic thinking, education and upbringing system, reforms, New Uzbekistan, Third Renaissance, youth upbringing, effectiveness of spiritual and educational work, development strategy, continuous spiritual upbringing.